THE EFFECT OF STOCKING DENSITIES ON GROWTH AND SURVIVAL OF BARRAMUNDI (Lates calcarifer Bloch, 1790) - Walusi, Risma; Nasution, Syafruddin; Zulkifli, Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conducted on 15 June-24 July 2019 in the Unit Pelaksana Teknis Daerah Balai Perikanan Budidaya Air Laut dan Payau (UPTD BPBALP Teluk Buo), West Sumatra. This study aims to determine the effect of stocking density and the best stocking density on growth and survival of Barramundi (Lates calcarifer) seeds. The method used in this study is an experimental method using a non factorial complete randomized design (RAL) with 4 treatments (A: 10 fish/8 liters, B: 20 fish/8 liters, C: 30 fish/8 liters, and D: 40 fish/8 liters) and 3 replications to produce 12 experimental units which were placed randomly. This study used a tub of fiber measuring 2.25 x 1.20 x 5.5 m3 and given a bulkhead using net measuring 20 x 20 x 20 cm3, amounting to 112 units with 4 mm net size and made of polyethylene. The test parameters in this study are absolute weight growth, absolute length increase, specific growth rate, survival rate, and water quality. The results of this study indicate that the best stocking density for growth and survival of Barramundi seeds is 20 fish/8 liters and the lowest is 40 fish/8 liters.Kata kunci: Stocking density, growth, survival, Lates calcarifer.